Union-HRM compability: an empirical assessment - Rozhan Othman, (Penerbit Universiti Kebangsaan Malaysia, 1997)
One view held by some researchers is that human resource management is a form of employee management practice which is anti-union. The emphasis on a strategic approach in human resource management implies that management's agenda should be accepted by all. This assumes that all parties in an organisation share a common interest. Unions are therefore seen as unimportant. In fact there is the view that the practice of human resource management is aimed at preventing the formation of unions. Empirical studies on this issue has result in different conclusions. This study is an empirical examination of the relationship between unions presence and human resource management practice.